Interrogating interneurone function using threshold tracking of the H reflex in healthy subjects and patients with motor neurone disease. Issue 8 (August 2020) - Howells, James; Sangari, Sina; Matamala, José Manuel; Kiernan, Matthew C.; Marchand-Pauvert, Véronique; Burke, David
CHighlights: Threshold-tracking H reflexes was used to study the excitability of soleus motoneurones. Presynaptic inhibition was lower in motor neurone disease, possibly due to an interneuronopathy. Hyperreflexia could reflect a spinal pre-motoneuronal abnormality. Abstract: Objective: The excitability of the lower motoneurone pool is traditionally tested using the H reflex and a constant-stimulus paradigm, which measures changes in the amplitude of the reflex response. This technique has limitations because reflex responses of different size must involve the recruitment or inhibition of different motoneurones. The threshold-tracking technique ensures that the changes in excitability occur for an identical population of motoneurones. We aimed to assess this technique and then apply it in patients with motor neurone disease (MND). Methods: The threshold-tracking approach was assessed in 17 healthy subjects and 11 patients with MND. The soleus H reflex was conditioned by deep peroneal nerve stimulation producing reciprocal Ia and so-called D1 and D2 inhibitions, which are believed to reflect presynaptic inhibition of soleus Ia afferents. Results: Threshold tracking was quicker than the constant-stimulus technique and reliable, properties that may be advantageous for clinical studies. D1 inhibition was significantly reduced in patients with MND. Conclusions: Threshold tracking is useful and may be preferable under some conditions for studying the excitability of the motoneurone pool. The decreased D1 inhibition in the patients suggests that presynaptic inhibition may be reduced in MND. Significance: Reduced presynaptic inhibition could be evidence of an interneuronopathy in MND. It is possible that the hyperreflexia is a spinal pre-motoneuronal disorder, and not definitive evidence of corticospinal involvement in MND.